Pariwisata Inklusif: Upaya Mewujudkan Kesetaraan dalam Pembangunan Pariwisata Indonesia - Rekta Deskarina (Ideas Publishing, 2026)
Inclusive tourism is a tourism development approach that emphasizes equal access, participation, and opportunities for all individuals. This study aims to examine the policies governing inclusive tourism development in Indonesia, as well as the implementation and challenges. The research adopts a qualitative approach using a systematic literature review (SLR) method by analyzing relevant legislation, government policy documents, and scholarly publications. The findings indicate that Indonesia has established a relatively strong policy framework to support the development of inclusive tourism. However, the implementation of these policies has not yet been fully optimized due to various challenge. The study is expected to provide valuable insights for policymakers in formulating more adaptive policies and developing effective implementation models to promote inclusive tourism in Indonesia.